The Analysis of Undercover Techniques by Involving in Narcotics Circulation Network - Bondan Satrio Bawono; Siti Rodhiyah Dwi Istinah; Aryani Witasari (Law Development Journal, 2022)
This study aims to find out and analyze how the undercover technique involves being involved in the narcotics distribution network to uncover cases at the Batang Police Resort. This study uses a sociological juridical approach and data collection through interviews, literature study and documentation. Based on the research, it was concluded that the Undercover technique by involving oneself in the narcotics distribution network to uncover cases at the Batang Police Resort was an attempt to enter into the narcotics distribution network and then lure the suspect in the operation target to leave by conducting narcotics transactions through the Undercover Buy technique or surrender. It was monitored and arrested before the transaction took place by ensuring that the suspected goods were in the possession of the suspect. The target of the technique is the elements of criminal acts as regulated in the Narcotics Law, such as the "whoever" element and the "controlling" element as well as the "circulating" element. The element of "whoever" is the target of the operation, in this case the suspect. The element of "control" means that it must be ensured that the alleged seller "controls" the narcotics goods. While the element of "circulating" is like selling narcotics. This technique was carried out because of the difficulty of uncovering the illicit trafficking of narcotics using a disconnected and neat system.